2018
DOI: 10.1038/s41598-018-35881-8
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of cadmium and lead in contaminated paddy field using inorganic and organic additives

Abstract: Heavy metal contamination of agricultural soils has posed a risk to environment and human health. The present study was conducted to assess the effectiveness of soil amendments for reducing cadmium (Cd) and lead (Pb) uptake by rice (Oryza sativa L) in a contaminated field. The soil amendments used include lime, DaSan Yuan (DASY), DiKang No.1 (DEK1), biochar, Fe-biochar, Yirang, phosphorus fertilizer, (Green Stabilizing Agent) GSA-1, GSA-2, GSA-3, and GSA-4, applied at 1% rate in a field experiment. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(32 citation statements)
references
References 52 publications
2
27
1
2
Order By: Relevance
“…Results from the principal correlation analysis revealed that Fe and Mn had a high negative correlation with Cd, As, Cr, and Pb in both plants and soil, while there was a strong positive correlation within HMs and metalloids. Our results were similar with [41,[84][85][86]. This indicates that Fe and Mn reduce the metal toxicity both in plants and soil.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Results from the principal correlation analysis revealed that Fe and Mn had a high negative correlation with Cd, As, Cr, and Pb in both plants and soil, while there was a strong positive correlation within HMs and metalloids. Our results were similar with [41,[84][85][86]. This indicates that Fe and Mn reduce the metal toxicity both in plants and soil.…”
Section: Discussionsupporting
confidence: 89%
“…The mobility of HMs were significantly decreased due to the application of lime that caused alkalinity in the soil; as a result, the precipitation and adsorption of HMs were enhanced. This adsorption and precipitation increased the stability of HMs and metalloids in soil [40,41]. Lee et al [42] used granulated lime (Ca(OH) 2 ) and calcium carbonate (CaCO 3 ) for removal of heavy metals from contaminated water and about 98% of As and 96% Cd were removed from the contaminated water through sweep precipitation.…”
Section: Discussionmentioning
confidence: 99%
“…The use of organic sorbents as remediative agents in soil has been questioned due to claims that they could be sources of contaminants including HMs. However, unlike other studies (Hamid et al 2018;Mbarki et al 2020) which found high HM concentrations in some organic sorbents (up to 5.7 mg kg −1 Cd, 12.9 mg kg −1 Pb and 116 mg kg −1 Zn), their contents in the sorbents used in this study were much lower and within acceptable range for use in soil systems (Barth et al 2008). Figures 1, 2 and 3 show the EDTA-extractable fractions of Cd, Pb and Zn, respectively, from soils contaminated with a mixture of HMs spiked into soil at three doses.…”
Section: Immobilisation Of Hms By Organic Sorbentscontrasting
confidence: 89%
“…Cd and Pb have received great concern (Fig. 2) because they are the primary pollutants in agricultural soils in many countries including China and Korea (Hamid et al 2018). An increasing research interest focused on engineered biochars, supported by various methods including physical, chemical and biological modifications in 2019.…”
Section: Heavy Metal Immobilizationmentioning
confidence: 99%